LOGISTICS EDUCATION IN TERMSOF INTEGRATION OF EDUCATION, SCIENCE, INDUSTRY AND BUSINESS - Vyacheslav M. Prikhod’Ko; Vitaliy V. Borshch; Zoya S. Sazonova (Высшее образование в России)
Discuss issues of training of graduates of transport logistics educational programs in the context of advanced professional activities. Context is modeled in terms established in MADI scientific and educational center of transport logistics «REC-TL.»